Assessing the Impact of Communications Strategy and Ethical Positioningon the Resilience of a Political Career Facing Scandal: Critical Analysis of Sexual Scandals within American Politics - Fisiak, Marta (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
Throughout the evolution of public political discourse we have repeatedly seen the effects of scandals on the careers of many politicians. Although the cultural and societal norms that have traditionally dictated the results of such scandals have changed dramatically within the last two centuries, I believe that the aftermath of these scandals may be better understood by analyzing and comparing the politician’s previously established public image to the scandal at hand. I will argue that a negative impact only occurs if and when there is a clear contradiction of character that presents the politician as a deceitful or hypocritical person in the media sphere and therefore the eyes of the public.